1992
DOI: 10.1016/1010-7940(92)90190-9
|View full text |Cite
|
Sign up to set email alerts
|

Early evidence of beneficial effects of chordal preservation in mitral valve replacement on left ventricular dimensions

Abstract: Earlier authors have shown the improved left ventricular (LV) function after chordae-preserving mitral valve replacement (MVR) in follow-up studies. Seventy-nine consecutive patients undergoing MVR were studied preoperatively and pre-discharge with M-mode and two-dimensional Color Doppler echocardiography for early LV morphometric changes. Conventional MVR was performed in 42 patients (Group 1) and the posterior leaflet-chordae-papillary muscle complex was preserved in 37 patients (Group 2). Both cohorts were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…2 In our study, patients undergoing MVR with resection of the anterior leaflet and its chordae (P-MVR group) had an increase in ESV, which differs from the 2 previous investigations. 16,23 Although Ghosh and colleagues 23 reported a fall in the median LV end-systolic dimension in 37 patients undergoing posterior chordal-sparing MVR, the difference was Ͻ5%. In a smaller cohort of 5 patients who underwent a similar type of MVR procedure, Hannein and associates 16 demonstrated a significant decrease in LV end-systolic dimension from 50 to 34 mm.…”
Section: Discussionmentioning
confidence: 99%
“…2 In our study, patients undergoing MVR with resection of the anterior leaflet and its chordae (P-MVR group) had an increase in ESV, which differs from the 2 previous investigations. 16,23 Although Ghosh and colleagues 23 reported a fall in the median LV end-systolic dimension in 37 patients undergoing posterior chordal-sparing MVR, the difference was Ͻ5%. In a smaller cohort of 5 patients who underwent a similar type of MVR procedure, Hannein and associates 16 demonstrated a significant decrease in LV end-systolic dimension from 50 to 34 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Ghosh et al [26] studied 79 patients undergoing MVR with complete chordal transection or posterior chordal preservation. The latter was found to be superior in terms of end systolic and diastolic dimensions.…”
Section: Human Echocardiographic (Physiological) Studiesmentioning
confidence: 99%
“…The conventional valve-replacement technique involves excision, with concomitant loss of the continuity between the valve annulus, valve tissue, chordae, and the ventricular wall. Clinical studies have shown, however, that preservation of the subvalvular apparatus plays an important role in maintaining ventricular performance after valve replacement [David 1983;Hennein 1990;Ghosh 1992]. Besides, the long-term outcome in corrected transposition of the great arteries is mainly determined by the function of the systemic ventricle, and consideration should be given to replacing the systemic atrioventricular valve at the earliest signs of progressive ventricular dysfunction.…”
Section: Discussionmentioning
confidence: 99%